2020
DOI: 10.1002/jmri.27132
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Prediction of High‐Grade Prostate Cancer via Biparametric MRI Radiomics

Abstract: Background Gleason score (GS) is a histologic prognostic factor and the basis of treatment decision‐making for prostate cancer (PCa). Treatment regimens between lower‐grade (GS ≤7) and high‐grade (GS >7) PCa differ largely and have great effects on cancer progression. Purpose To investigate the use of different sequences in biparametric MRI (bpMRI) of the prostate gland for noninvasively distinguishing high‐grade PCa. Study Type Retrospective. Population In all, 489 patients (training cohort: N = 326; test coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Second, some factors or receptors related to PCa progression, such as CXC chemokine receptor 4 (CXCR4), are overexpressed in areas composed of approximately 40–60% of tumor glands rather than at the tumor center 39 . Although many studies have used MR radiomics analyses for the assessment of GS grading, only Gong et al 40 used manual segmentation of the whole prostate gland to construct a biparametric (T2WI + DWI) MR radiomics model for the prediction of high‐grade PCa. Their model achieved an AUC of 0.788 in the test cohort, but the performance did not improve after the incorporation of clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…Second, some factors or receptors related to PCa progression, such as CXC chemokine receptor 4 (CXCR4), are overexpressed in areas composed of approximately 40–60% of tumor glands rather than at the tumor center 39 . Although many studies have used MR radiomics analyses for the assessment of GS grading, only Gong et al 40 used manual segmentation of the whole prostate gland to construct a biparametric (T2WI + DWI) MR radiomics model for the prediction of high‐grade PCa. Their model achieved an AUC of 0.788 in the test cohort, but the performance did not improve after the incorporation of clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the choice of large set of features may help in distinguishing disease pathophysiology better and hence likely improve prediction than a small set of features, which may miss certain tissue characteristics. [34][35][36][37][38] Furthermore, we employed opensource software and provide access to datasets as well as details on our feature pruning/selection process to ensure comparability and transparency. However, direct comparison of our results with prior studies is limited since none of prior studies applying radiomics and machine learning methods for prostate MRI provide access to datasets and postprocessing code.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported similar ( p = 0.83) diagnostic performance of biparametric MRI without DCE (pooled sensitivity and specificity of 0.74 and 0.90, respectively) and mpMRI (pooled sensitivity and specificity of 0.76 and 0.89, respectively) for the diagnosis of PCa, suggesting the former as a valuable first-line imaging test due to its robust sensitivity [ 84 ]. Notably, Gong et al have recently reported the high diagnostic performance of radiomic models based on biparametric MRI to non-invasively identify high-grade PCa, with accuracy ranging from 0.787 and 0.801 [ 85 ]. However, despite the limited role of DCE in determining the overall PI-RADS category, in some instances DCE may assist in the detection of PCa and the PI-RADS Committee suggests to reserve biparametric MRI only for selected clinical scenarios.…”
Section: Prostatementioning
confidence: 99%